ChemInform Abstract: Palladium‐Catalyzed Cascade Reactions of 1‐(3‐Arylprop‐2‐ynyloxy)‐2‐bromo Benzene Derivatives with Organoboron Compounds. Issue 35 (8th August 2013) - Arcadi, Antonio; Blesi, Federico; Cacchi, Sandro; Fabrizi, Giancarlo; Goggiamani, Antonella; Marinelli, Fabio
Abstract The methodology allows a new access to various 2‐unsubstituted, 3‐functionalized benzofuran skeletons.